BENTUK ALTERNATIF PENGELOLAAN KARYA MUSIK MELALUI MEDIA BARU (Studi Kasus Euforia Records Dalam Mengelola Promosi dan Distribusi Album âAngka 8â Band Endank Soekamti) - , Nala Nandana Undiana, Dr. phil. Hermin Indah Wahyuni, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis discusses the management of an independent music industry in Indonesia. A lot of the actors and creative worker in Indonesia, finnaly faced the obstacles such as lack of financial capital to survive in the dynamic of the music industry. As a new alternative, independent music management can be an alternative choice for new commers to be able in this music industry which already falling apart. Using a case study of Euforia Records, which is one of the many independent music labels in Yogyakarta, this thesis tries to explore various alternatives in the promotion and distribution of music content. With the support from the development of new media at this time, the alternative pattern is expected to open the way and opportunities for musicians to be struggle without depending and waiting for the opportunities offered by the convensional music industry. This thesis combines the fact of qualitative research and discourse from the future of community interaction which ultimately entering the digital age in the new media era.